Value judgment of life quality of women diagnosed with HIV/AIDS in Maceio, Alagoas, Brazil - Cecilio Argolo Júnior; Sonia Maria Soares Ferreira; Vívian Wanderley Teixeira de Albuquerque; Jessyca Ítala Barros Wanderley da Silva (O Mundo da Saúde)
The risk of contamination by HIV virus has been increasing between heterosexual partners, affecting mainly poor women from rural areas. To study the quality of life of these epidemiologically and socially vulnerable women may be a way to allow the construction of a new panorama about their psychic, emotional and social health in face of this disease. The objective of this study was to verify the quality of life (Q-L) of women having HIV/AIDS that attended a reference center (Maceió-AL). 154 women were interviewed from April to October 2013. For this data collection, a questionnaire containing some sociodemographic and clinical aspects and the inventory HIV/ AIDS –Target Quality of Life (HAT – QoL) was used. Women interviewed were 37-38 years old (± 10.49); having low formal education; and low income (90.2%). 78.6% had recent infection; and 71.4% use antiretroviral medication. The average areas that make up the HAT-QoL ranged from 27.3 to 83.7. Within the nine areas, seven of them had average ≤ 50.0. Within the construct sensing we observed significant evaluations concerning life satisfaction, concerns about health, financial worries, trust, and sexual function and the following sociodemographic and clinical characteristics: Income, school timing, formal education, work incapacity due to HIH, having a partner, CD4 count and viral load. The results show low quality of life of the women interviewed. The most affected areas were mostly concerns about confidentiality, finances, acceptance of HIV and life satisfaction. These results may contribute to the improvement of quality of life and comprehensive care in health and the right of their citizenship.